2022
DOI: 10.1016/j.ijpx.2021.100109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mAb and excipient cryoconcentration on long-term frozen storage stability – part 2: Aggregate formation and oxidation

Abstract: We examined the impact of monoclonal antibody (mAb) and buffer concentration, mimicking the cryoconcentration found upon freezing in a 2 L bottle, on mAb stability during frozen storage. Upon cryoconcentration, larger protein molecules and small excipient molecules freeze-concentrate differently, resulting in different protein to stabiliser ratios within a container. Understanding the impact of these shifted ratios on protein stability is essential. For two mAbs a set of samples with constant mAb (5 mg/mL) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The authors went on to show that the protein and small excipients freeze-concentrate differently, resulting in different local protein to stabilizer ratios within a container, ultimately leading to mAb instability under these storage conditions. 18 Interestingly, Bluemel et al 19 have recently reported on the use of computational fluid dynamic (CFD) simulations of mAb solutions. They conclude that CFD simulations are a promising tool to describe large-scale freezing and thawing of mAb solutions and could potentially save time and resources.…”
Section: Aggregationmentioning
confidence: 99%
“…The authors went on to show that the protein and small excipients freeze-concentrate differently, resulting in different local protein to stabilizer ratios within a container, ultimately leading to mAb instability under these storage conditions. 18 Interestingly, Bluemel et al 19 have recently reported on the use of computational fluid dynamic (CFD) simulations of mAb solutions. They conclude that CFD simulations are a promising tool to describe large-scale freezing and thawing of mAb solutions and could potentially save time and resources.…”
Section: Aggregationmentioning
confidence: 99%
“…[16][17][18][19] Solidification is initiated by ice nucleation, which is a stochastic process, 16,17,[20][21][22][23][24] leading to variability in freezing behavior among vials even if their thermal environment is identical. 16,18,19,23,25,26 Based on these considerations, freezing may be characterized by three quantities, which are conceptually linked to most of the known degradation mechanisms for frozen biopharmaceuticals: [7][8][9][10]18,19,[27][28][29][30][31] These are the nucleation time, i.e. the duration of the liquid state; the nucleation temperature, which is interpreted as predictor for the ice crystal morphology in the frozen product; 19,27 and the solidification time, which is the duration of the partially frozen state and connected to the phenomenon of freeze-concentration.…”
Section: Introductionmentioning
confidence: 99%
“…the duration of the liquid state; the nucleation temperature, which is interpreted as predictor for the ice crystal morphology in the frozen product; 19,27 and the solidification time, which is the duration of the partially frozen state and connected to the phenomenon of freeze-concentration. [28][29][30][31] In case a drug product exhibits a relevant degradation mechanism related to freezing, these three quantities should be considered during development, implying that all vials meet qualified target ranges with sufficient probability.…”
Section: Introductionmentioning
confidence: 99%